(untitled) (Cultura Económica, 2018)
This paper explores the nature of wisdom and provides research insights into how practical wisdom might be understood and practiced by managers. In the first place, the author sets out the academic and research context for wisdom and ‘phronetic research’ and then utilizes the methodology of Social Practice Wisdom (SPW) to analyze the survey results of 181 senior executives when they were asked what wisdom meant for them and how wisdom worked in the practice of managerial decision-making.